Effects of different phenylcapsaicin doses on neuromuscular activity and mechanical performance in trained male subjects: a randomized, triple-blinded, crossover, placebo-controlled trial - Jiménez-Martínez, Pablo; Sánchez-Valdepeñas, Juan; Cornejo-Daza, Pedro J.; Cano-Castillo, Clara; Asín-Izquierdo, Iván; Alix-Fages, Carlos; Pareja-Blanco, Fernando; Colado, Juan C. (Frontiers in Physiology, 2023)
Objective: This study aimed to examine the effects of phenylcapsaicin (PC) supplementation on strength performance and neuromuscular activity in young trained male subjects. Materials and methods: A total of 25 trained subjects [full-squat (SQ) one repetition maximum (1RM) = 125.6 ± 21.0 kg] were enrolled in this randomized, triple-blinded, crossover, placebo-controlled trial. The subjects performed a first session and a post-24 h session for each condition. In the first session, the subjects ingested a high dose of PC (HD, 2.5 mg), a low dose (LD, 0.625 mg), or a placebo (PLA). Their performance in SQ was assessed under a 3% × 8 × 70% 1RM protocol in the first session. Their performances in countermovement jump (CMJ), SQ with 60% 1RM, and isometric squat were measured before and after the SQ protocol in both sessions. The neural activity of the vastus lateralis (VL) and vastus medialis (VM) was recorded via surface electromyography (EMG) and averaged in both sessions. Results: Significant differences between the conditions were reported for lifting velocity, velocity loss, and the 60% load in dynamic SQ (p range = 0.02–0.04). Electrical changes were not identified for any outcome, although neural activity changed across time (p range ≤0.001–0.006). A significant condition × time effect was observed in CMJ compared to PLA (p ≤0.001) and LD (p ≤0.001). Intra-set analyses revealed higher velocities in HD compared to those in LD (p = 0.01) and PLA (p range = 0.004–0.008). Conclusion: Therefore, PC may improve the strength performance and attenuate the mechanical fatigue induced by resistance training in SQ and CMJ exercises.